Copper-catalysed benzofuran synthesis: developing aryl bromide-alkenyl triflates as general heterocycle precursors - Tadd, A; Fielding, MR; Willis, M (2007)
A range of conjugated aryl bromide-alkenyl triflates, previously described as indole precursors, are efficiently converted to the corresponding benzofurans when treated with CuI/TMEDA and potassium hydroxide. © 2007 Elsevier Ltd. All rights reserved.